Cities and Urban Regions Under Change. Between Vulnerability, Resilience, Transition and Transformation. [Editorial] - Deppisch, Sonja (Springer Fachmedien, 2017)
Different conceptual approaches as well as terms are applied if one looks at how or if cities and their surrounding region are dealing with past, current and future known as well as unknown change processes, their potential impacts and the consequential challenges they evoke. Dominant concepts in this recent discussion seem to be vulnerability, resilience and transition or for the latter also transformation. All of these three are more or less contested concepts with many different understandings. This chapter gives a brief introduction and overview of the discussion as well as of the interlinkages between the conceptualizations used in this book.
Keywords: Stadtregion; Stadt; Resilienz; Vulnerabilität; Transformation; Nachhaltigkeit; Stadtentwicklung; Konzept